Analisis Faktor-Faktor Yang Mempengaruhi Auditor Dalam Melakukan Audit Judgement (Studi Empiris Pada Kantor Akuntan Publik di Jawa Tengah dan DIY). - Rahmawati, Novita; , Dr. Zulfikar, SE, M.Si (2016)
This research aimed to analyze the influence of gender, obedience pressure, task complexity, ethical perception and auditor's experience toward audit judgment taken by auditor This research was a quantitative one. Data were collected through a survey by using questionnaires. The population of this research are all auditors working on the CPA's in Jawa Tengah and DIY. The sample of this research are 50 auditors working on the CPA's in Jawa Tengah and DIY. Determination of samples by using convenience sampling method. The analysis method of this research using multiple regression analysis. The result of this research indicate that gender, obedience pressure, task complexity, ethical perception and auditor's experience have an influance on the audit judgment taken by auditor